EFFORTS TO OVERCOME CRIMINAL ACTS OF NARCOTICS ABUSE - Mhd. Ihwanuddin Hasibuan; Andry Syafrizal Tanjung (Universitas Efarina, 2023)
Narcotics abuse has a very bad impact on the continuity of a nation's generations. To anticipate this, cooperation from all components of society, such as families, from school to university level, and the government must be united in efforts to prevent narcotics in the surrounding environment. The formulation of the research problem is: 1) How is the police investigation process organized for perpetrators of narcotics abuse? 2) What efforts are made by law enforcers to prevent narcotics abuse? This is a normative research with sources of legal materials in this research being primary and secondary legal materials, techniques for collecting legal materials using documentation recording methods and reading statutory regulations related to the problem and analyzed using qualitative descriptive. From the results of observations and research, the police were given authority to carry out investigations and investigations up to the filing of P-21, the Police carry out investigations if there is a report; caught. The implementation of the investigation originates from three things as stated in the Criminal Procedure Code, steps that must be taken by all levels of society in efforts to prevent and control Narcotics in the community, including: 1. Promotive Methods, 2. Preventative Methods, 3. Repressive Methods, 4. Curative Methods, 5 Rehabilitation.